2010
DOI: 10.1590/s1413-70542010000500005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação e remoção de cobre em aguardentes de cana pela utilização dos aluminossilicatos: zeólita e bentonita

Abstract: RESUMOA cachaça, bebida genuinamente nacional, é um produto de grande aceitação nos mercados interno e externo. Durante o processo de produção há alguns pontos críticos, ocorrendo a formação de contaminantes que podem afetar a qualidade da bebida, sendo necessário o conhecimento de sua composição química. Com este trabalho, objetivou-se comparar o comportamento do cobre, quando presente em solução alcoólica 40% e uma aguardente comercial (utilizando sulfato de cobre pentaidratado como fonte desse mesmo metal),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…These results confirm those of other authors who used other matrices and even bentonite clay as an adsorbent medium for copper in cachaça (Lima et al, 2009;Cantão et al, 2010). However, it is known that the reduction in the concentrations of aldehydes, higher alcohols and esters with filtration, whatever the adsorbent, can often modify the bouquet of the cachaça because these elements impart a different bouquet to the beverage when present in appropriate concentrations.…”
Section: Adsorption Isothermssupporting
confidence: 89%
See 4 more Smart Citations
“…These results confirm those of other authors who used other matrices and even bentonite clay as an adsorbent medium for copper in cachaça (Lima et al, 2009;Cantão et al, 2010). However, it is known that the reduction in the concentrations of aldehydes, higher alcohols and esters with filtration, whatever the adsorbent, can often modify the bouquet of the cachaça because these elements impart a different bouquet to the beverage when present in appropriate concentrations.…”
Section: Adsorption Isothermssupporting
confidence: 89%
“…This can be explained by the adsorption of the aldehydes through the contact with the clays, or to a lesser extent, by the oxidation of aldehydes to the corresponding carboxylic acids, as well as their possible loss through evaporation during the filtering process. Comparing the results obtained by Lima et al (2006;Cantão et al (2010), it can be concluded that the results obtained in our research are within the expected, presenting a slight decrease of this component.…”
Section: Adsorption Isothermssupporting
confidence: 88%
See 3 more Smart Citations